2016
DOI: 10.5897/ajar2015.9715
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for selecting soybean genotypes using mixed models and multivariate approach

Abstract: The objective of this study was to select soybean genotypes derived from crosses between conventional and transgenic lines Roundup Ready (RR), using jointly Restricted Maximum Likelihood/Best Linear Unbiased Prediction (REML/BLUP) approaches, factors analysis and principal components analysis, processed with favorable agronomic traits, during the 2013/2014 growing season. Three agronomic selection processes were identified to select genotypes that discriminate genotypes containing more specific properties. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Interaction analysis allows the maximization of selection gains, when testing homozygous clones or lines. Similar results were obtained by other authors (Pinheiro et al, 2013;Rocha et al, 2015;Andrade et al, 2016), who also found low-heritability estimates for soybean GY. The value of interaction variance (V G×A ), when higher than the genotypic variance (V G ), also contributes to the low values of the h 2 g estimates.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interaction analysis allows the maximization of selection gains, when testing homozygous clones or lines. Similar results were obtained by other authors (Pinheiro et al, 2013;Rocha et al, 2015;Andrade et al, 2016), who also found low-heritability estimates for soybean GY. The value of interaction variance (V G×A ), when higher than the genotypic variance (V G ), also contributes to the low values of the h 2 g estimates.…”
Section: Resultssupporting
confidence: 92%
“…The simultaneous use of mixed models based on REML/BLUP and multivariate methods enables the exploration of different adaptability and stability concepts, thereby complementing the collected data, thus increasing the efficacy of the selection of superior genotypes (Andrade et al, 2016). This study differs from other published ones on the parameters of soybean adaptability, stability, and yield performance because it combines the methods of mixed-models and GGE biplots, in order to assess cultivars widely grown in the Brazilian macroregions of adaptation 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…Andrade et al. (2016) studied F 6 generation soy strains in Jaboticabal, SP, Brazil, and obtained higher CV estimates for a number of branches (69.5%), whereas Oliveira et al. (2019), studying the genetic diversity of soy strains developed by the genetic improvement program of the Federal University of Tocantins aiming at biodiesel production, reported CVs ranging from 2.5 to 28.2% for the agronomic characters evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The mixed model has been applied to the analysis of cultivar trial data for many crops such as soybean (Andrade et al 2016), corn (So and Edwards 2009; Hu and Spilke 2011), wheat (Friesen et al 2016), rape (Hu et al 2014), and canola (Beeck et al 2010). Results are not always consistent due to differences in crop cultivars, trial environments, adopted variance-covariance structure of models, and data sufficiency.…”
Section: Introductionmentioning
confidence: 99%